Oncostatin M’s Involvement in the Pathogenesis of Chronic Rhinosinusitis: Focus on Type 1 and 2 Inflammation - Chie Ishikawa; Sachio Takeno; Yukako Okamoto; Tomohiro Kawasumi; Takashi Kakimoto; Kota Takemoto; Manabu Nishida; Takashi Ishino; Takao Hamamoto; Tsutomu Ueda; Akio Tanaka (Biomedicines, 2023)
Objectives: The cytokine oncostatin M (OSM) elicits pathogenic effects involving disruption of the epithelial barrier function as a part of immunological response networks. It is unclear how these integrated cytokine signals influence inflammation and other physiological processes in the pathology of chronic rhinosinusitis (CRS). We investigated the expression and distribution of OSM and OSM receptor (OSMR) in CRS patients’ sinonasal specimens, and we compared the results with a panel of inflammatory cytokine levels and clinical features. Patients and Methods: We classified CRS patients as eosinophilic (ECRS, n = 36) or non-eosinophilic (non-ECRS, n = 35) based on the Japanese Epidemiological Survey of Refractory Eosinophilic Chronic Rhinosinusitis phenotypic criteria and compared their cases with those of 20 control subjects. We also examined OSM’s stimulatory effects on cytokine receptor expression levels using the human bronchial epithelium cell line BEAS-2B. Results: RT-PCR showed that the OSM mRNA levels were significantly increased in the CRS patients’ ethmoid sinus mucosa. The OSM mRNA levels were positively correlated with those of TNF-α, IL-1β, IL-13, and OSMR-β. In BEAS-2B cells, OSM treatment induced significant increases in the OSMRβ, IL-1R1, and IL-13Ra mRNA levels. Conclusions: OSM is involved in the pathogenesis of CRS in both type 1 and type 2 inflammation, suggesting the OSM signaling pathway as a potential therapeutic target for modulating epithelial stromal interactions.